Art Brussels 2001 : 19th Contemporary Art Fair. - Doove, Edith; Everard, Eric; Art Brussels 2001 (Brussel : Artexis nv. Brussel, 2001)
Aguirre y Otegui, Philip ; Appelt, Dieter ; Arink, Karin ; Arkesteyn, Maddy ; Armleder, John ; Ayres, Tim ; Bartoloméo, Joël ; Bayliss, Sean ; Bervoets, Fred ; Besson, Jacky ; De Beul, Bert ; Bichaud, Jean-Luc ; Bonde, Niels ; Buetti, Daniele ; Bürkle, Stefanie ; Buylen, Michel ; Chaissac, Gaston ; Chelushkin, Kirill ; Chen Zhen ; Chia, Sandro ; Chillida, Eduardo ; Christinat, Olivier ; Clark, Larry ; Craig, Stephen ; Delvoye, Wim ; Desjardin, Arnaud ; diCorcia, Philip-Lorca ; Dormice ; van Elk, Ger ; Eyberg, Sylvie ; Fabre, Jan ; De Felipe, Antonio ; Fonchain, Jérôme ; Foote, Huger ; Friedmann, Gloria ; Frieling, Gijs ; Gadenne, Bertrand ; Gage, Jenny ; Ganis, Maurice ; Geenen, Lajos ; Gerard, Pierre ; Geuenich, Georg ; Geys, Jef ; Gfeller, Catherine ; Gianni, Giordano ; Gijzen, Robbert-Jan ; De Gobert, Philippe ; Goldsworthy, Andy ; Goossens, Marnix ; Helg, Béatrice ; Henning, Anton ; Hermans, Renoît ; Hernandez Pijuan, Juan ; Hernandez, Anthony ; Hilgemann, Ewerdt ; Holland, David ; Horn, Rebecca ; Horn, Roni ; Hütte, Axel ; Hyber, Fabrice ; Hyde, James ; Ivens, Renaat ; Kelley, Mike ; Kirkeby, Per ; Klein, Micha ; Komen, A.P. ; Königsfeld, Dirk ; Koster, Jan ; Kounellis, Jannis ; Krijnen, Cees ; Krystufek, Elke ; Laib, Wolfgang ; Lasker, Jonathan ; Lee, Hatty ; Leisgen, Barbara & Michael ; Lengner, Matthias ; Lück, René ; Ma Liuming ; MacDonald, Euan ; Mahieu, Didier ; Maltz, Russell ; Männikkö, Esko ; Marcel, Didier ; Martinez, César ; Maryan, Maryan S. ; Maurer, Helen ; McCarthy, Paul ; McGinn, Martin ; Mencoboni, Didier ; Mercier, Mathieu ; Meyer, Harding ; Michels, Alex ; Miller, Gerold ; Moffatt, Tracey ; Morellet, François ; Mortier, Antoine ; Mréjen, Valérie ; Murphy, Karen ; Myung-OK, Han ; Nagels, Jens ; O'Donoghue, Hughie ; etc.
Engels
Frans
Nederlands
Art Brussels 2001 : 19th Contemporary Art Fair, Brussels Expo Brussel, Artexis nv. Brussel, 20.04 - 24.04.2001
boek